THE IMPLEMENTATION OF REGIONAL CYBERSECURITY EFFORTS IN ASEAN TOWARDS A RESILIENT CYBERSECURITY AMID THE ASEAN MEMBER COUNTRIES' DIGITAL DIVIDE - Harryanto Aryodiguno; Stevavni Tandean (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
Technological development has brought changes to all aspects of life. Southeast Asia is a region with a large population and considerable economic potential. With the growth of technology, Southeast Asian countries have become highly dependent on the digital world, which in turn supports the region's developing digital economy. Therefore, cybersecurity and cyber resilience are essential to prevent cyberattacks and to limit their impact when they do occur. For this reason, Southeast Asian countries have joined a regional organization, ASEAN, committed to building regional peace and stability, including in the area of cybersecurity. However, in building resilient cybersecurity, ASEAN faces the digital divide among its member states as an obstacle that may hinder these efforts. This issue is raised because detailed discussion of cybersecurity in Southeast Asia remains limited. This research therefore examines how ASEAN builds resilient cybersecurity despite the digital divide among its member states, using a qualitative method, analyzed through liberalism theory, and closed with recommendations.